Dance as Environmental Advocacy: A Study of What Goes Around Comes Around in Nigeria - Yusuf, Hairat Bukola (Journal of Dance and Dance Education Studies, 2025)
Nigeria continues to face severe environmental challenges such as improper waste disposal, air pollution and water contamination, despite numerous laws and policies. However, these measures often fail to inspire lasting behavioural change due to weak emotional connection with the public. Therefore, this study critically examines What Goes Around Comes Around, a dance performance by the Nbari Nbajo Dance Troupe, as a creative intervention for environmental awareness and behavioural transformation. The study adopted a qualitative approach, using direct observation of live performance, Focus Group Discussions (FGD) with audience members and Key Informant Interviews (KIIs) with choreographer and dancers. Data gathered were analysis thematically to explore how the performance communicates the consequences of pollution and motivates audiences toward sustainable practices. Findings reveal that the performance effectively raises environmental awareness through symbolic dance movements and emotional appeal which stimulate reflection and dialogue among audience members. The study argues that integrating dance into environmental advocacy promotes deeper emotional connection and fosters sustainable behavioural change beyond conventional policy-driven approaches.